Socio-Exegetical Interpretation of 1 Kings 17:13b within the Context of Nigerian Economic Vulnerability and Clerical Authority - Ogunbiyi, David Oluwabukunmi (Darul Yasin Al Sys, 2025)
Religion in Nigeria functions as both a source of empowerment and a mechanism of exploitation, particularly within the context of widespread poverty, inflation, and post-COVID socio-economic instability. With over 90 million Nigerians living below the poverty line, Christian clergy have emerged as influential figures not only in spiritual matters but also in economic and psychological spheres. This study examines the intersection of clerical authority and economic vulnerability in Nigerian Christianity through a socio-exegetical analysis of 1 Kings 17:13b, the account of Elijah and the widow of Zarephath. This passage is frequently employed in Nigerian churches to promote sacrificial giving, often presented as a demonstration of faith with the promise of divine reward. However, concerns have been raised regarding the potential manipulation of impoverished or widowed congregants under such teachings. By drawing contextual parallels between the widow’s plight and that of many Nigerian believers, this research explores the theological implications and ethical challenges of applying this text in contemporary preaching. Using a mixed-methods approach, the study combines biblical exegesis with empirical data collected from 274 clergy and laity respondents. The findings reveal a divide: while many interpret Elijah’s request as a test of faith affirming prophetic authority, others caution against its exploitation for personal or institutional gain. Respondents also stress the importance of embodying Elijah’s compassion and tangible support, not merely spiritual exhortation. The study concludes that interpretations of 1 Kings 17:13b must be grounded in pastoral ethics, particularly in economically vulnerable contexts. Churches are urged to promote accountability, encourage voluntary giving, and invest in robust welfare initiatives to fulfill their holistic mission as both spiritual leaders and agents of social support.